Risk factors for recurrence of endometrial hyperplasia in women of late reproductive and premenopausal age - С. М. Корниенко (Репродуктивная эндокринология, 2017)
According to many researchers, hyperplastic endometrial processes are not precancerous diseases. However, recurrent endometrial hyperplastic processes, as well as their combination with genital and extragenital pathologies, significantly increase the risk of malignant transformation of the endometrium. Late reproductive and premenopausal age is associated with an increase in the frequency of endometrial hyperplastic processes, extragenital pathology and operative interventions on the internal genitalia. The limited possibilities of conservative treatment in connection with concomitant diseases and the tendency of an increase in the recurring hyperplastic processes of the uterus make the problem of studying various aspects of hyperplastic endometrial processes in women of this age period extremely urgent.